2016
DOI: 10.1002/lpor.201600064
|View full text |Cite
|
Sign up to set email alerts
|

Metamaterial absorber integrated microfluidic terahertz sensors

Abstract: Spatial overlap between the electromagnetic fields and the analytes is a key factor for strong light-matter interaction leading to high sensitivity for label-free refractive index sensing. Usually, the overlap and therefore the sensitivity are limited by either the localized near field of plasmonic antennas or the decayed resonant mode outside the cavity applied to monitor the refractive index variation. In this paper, by constructing a metal microstructure array-dielectric-metal (MDM) structure, a novel metam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
130
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 254 publications
(134 citation statements)
references
References 66 publications
3
130
0
Order By: Relevance
“…Sensing performance of triple-band absorber (in terms of the surrounding refractive index, thickness and refractive index changes of the overlayer) is also analyzed. The results demonstrate that the FOM (figure of merit) of the third resonance peak can be up to 40.67, which is much larger than previously reported works [43][44][45][46][47][48][49][50], see Table 1. More importantly, we found that besides the frequency shifts with the change of the refractive indexes of the surrounding, the absorbance of the third resonance peak has an apparent change.…”
Section: Introductionmentioning
confidence: 48%
“…Sensing performance of triple-band absorber (in terms of the surrounding refractive index, thickness and refractive index changes of the overlayer) is also analyzed. The results demonstrate that the FOM (figure of merit) of the third resonance peak can be up to 40.67, which is much larger than previously reported works [43][44][45][46][47][48][49][50], see Table 1. More importantly, we found that besides the frequency shifts with the change of the refractive indexes of the surrounding, the absorbance of the third resonance peak has an apparent change.…”
Section: Introductionmentioning
confidence: 48%
“…In 2016, Hu et al constructed a metal microstructure array-dielectricmetal structure integrated with microfluidic. The sensitivity of their structure is 3.5 THz shifting per Refractive Units Index(THz/RIU) [33]. In 2017, Geng et al integrated two kinds of THz metamaterials biosensor with microfluidics as shown in Fig.…”
Section: Treatment Of Biomedical Samplementioning
confidence: 99%
“…[85] Such microfluidic channels can sensitively capture the target samples only in an aqueous environment, avoiding huge signal loss by water absorption. [86][87][88] Combining the high-quality factor of resonators and microfluidic channels, several chemicals, biomarkers, or cells in a solution state could be detected. Another suggestion for improving the efficiency of a metamaterial sensing chip is to capture a specific molecule using the structure of a 2D thin film, such as graphene.…”
Section: Wwwadvopticalmatdementioning
confidence: 99%